2019
DOI: 10.14814/phy2.13978
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-stimulated arterial transit time in calf muscles measured by dynamic contrast-enhanced magnetic resonance imaging

Abstract: The primary goal of this study was to evaluate arterial transit time (ATT) in exercise‐stimulated calf muscles as a promising indicator of muscle function. Following plantar flexion, ATT was measured by dynamic contrast‐enhanced (DCE) MRI in young and elderly healthy subjects and patients with peripheral artery disease (PAD). In the young healthy subjects, gastrocnemius ATT decreased significantly (P < 0.01) from 4.3 ± 1.5 to 2.4 ± 0.4 sec when exercise load increased from 4 lbs to 16 lbs. For the same load of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…Our data also enabled the assessment of ATT, which was shown to be shorter just after exercise, increasing over time thereafter, and was shorter in the proximal compared with the distal slice during the first 2 min of recovery. The shorter ATT just after exercise is in line with previous work using dynamic contrast‐enhanced imaging showing that ATT decreases with increasing workload 14 . More specifically, we found that the ATT was shorter just after exercise, meaning that the labeled blood travels faster to the imaged region.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data also enabled the assessment of ATT, which was shown to be shorter just after exercise, increasing over time thereafter, and was shorter in the proximal compared with the distal slice during the first 2 min of recovery. The shorter ATT just after exercise is in line with previous work using dynamic contrast‐enhanced imaging showing that ATT decreases with increasing workload 14 . More specifically, we found that the ATT was shorter just after exercise, meaning that the labeled blood travels faster to the imaged region.…”
Section: Discussionsupporting
confidence: 91%
“…The shorter ATT just after exercise is in line with previous work using dynamic contrast-enhanced imaging showing that ATT decreases with increasing workload. 14 More specifically, we found that the ATT was shorter just after exercise, meaning that the labeled blood travels faster to the imaged region. As a result, the peak ASL signal is reached F I G U R E 5 The average Buxton fit for each time window over all participants after exercise for the proximal and distal slice.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation